New Clinical Nursing Supervision with 2P Safety: Concept and Application - Cheevakasemsook, Aree (Journal of The Royal Thai Army Nurses, 2020)
The globalization era lead borderless data linkages to easy accessibility to digital technology and information. This enhances the majority of people get wider and deeper knowledge, and have higher demands and expectations on healthcare services. Healthcare personnel should contemplate their own cognition and operational processes to sustain quality along with patient safety. Therefore, to develop nursing personnel competencies aligned with this change is extremely essential. Head nurses have to do supervise how to practice 2P safety basis (Patient and Personnel Safety) which is the new concept corresponding to policies of Ministry of Public Health to drive both patient and personnel safeties. This article intends to delineate nursing supervision on clinical safety with the 2P principle through short words as “SIMPLE” so that primary nursing managers could figure out and do further application.